PENGGUNAAN BAHASA INDONESIA DIKALANGAN REMAJA - Ni Putu Andini Desiyanti Laksmi; I Nyoman Bawa Bagiada (Yayasan Nusantara Hasana Berdikari, 2026)
The Indonesian language plays a significant role in the country's cultural and national identity. Demonstrating pride in using Indonesian is one way to demonstrate respect for Indonesia's cultural heritage and linguistic diversity. It also reflects a sense of respect for national unity through language, which serves as a means of shared communication. Today, the millennial generation is increasingly familiar with social media and digital technology. This has impacted the evolution of the Indonesian language among young people, often incorporating slang and foreign language terms. The influence of foreign cultures through songs and films such as K-Pop and Korean dramas, as well as other foreign cultures, also contributes. This creates a stigma among them, where the use of foreign language in speech, such as saying